Micro-mechanical evaluation of SiC-SiC composite interphase properties and debond mechanisms. (15th December 2017) - Kabel, J.; Yang, Y.; Balooch, M.; Howard, C.; Koyanagi, T.; Terrani, K.A.; Katoh, Y.; Hosemann, P.
Abstract: SiC-SiC composites exhibit exceptional high temperature strength and oxidation properties making them an advantageous choice for accident tolerant nuclear fuel cladding. In the present work, small scale mechanical testing along with AFM and TEM analysis were employed to evaluate PyC interphase properties that play a key role in the overall mechanical behavior of the composite. The Mohr-Coulomb formulation allowed for the extraction of the internal friction coefficient and debonding shear strength as a function of the PyC layer thickness, an additional parameter. These results have led to re-evaluation of the Mohr-Coulomb failure criterion and adjustment via a new phenomenological equation.